Tata Cara Pembagian Harta Warisan Peninggalan Suami Terhadap Janda di Desa Sigi Kabupaten Pulang Pisau - Yetno, Alfred; Rahmawati, Ni Nyoman (Belom Bahadat, 2024)
In the midst of rapidly changing social dynamics, it is crucial to recognize the rights of women or widows as heirs by ensuring that they receive a fair share of inheritance in accordance with their contributions and roles in building the family and household. Therefore, there is a need for awareness regarding the protection of the rights of women or widows in the context of inheritance law, allowing them to receive fair and equal treatment in the distribution of inherited assets. This is a significant step towards achieving gender equality and justice in Indonesian society. This research focuses on examining and understanding the complex issues related to the procedures for the distribution of the inheritance of a deceased husband to a widow in the village of Sigi, Pulang Pisau Regency, Central Kalimantan Province. The study aims to provide profound insights into the practices and perspectives of the community regarding customary inheritance law and its influence on the rights of women or widows in inheriting their husband's estate. Through this research, it is hoped that solutions can be found to address the injustice often faced by women or widows in inheritance distribution. Additionally, the study aims to provide policy recommendations to enhance the protection of the rights of women or widows in the community. The method employed is empirical legal research using a qualitative approach. The conclusion drawn from the research is that the inheritance law system in the village of Sigi, Kahayan Tengah District, Pulang Pisau Regency, prioritizes customary inheritance law in the distribution of inherited assets by upholding noble values based on the principle of family solidarity. This is done through consensus and the distribution of inherited assets to all surviving family members, including widows or widowers and legitimate children or their descendants. The process is conducted fairly and evenly through family consensus and the eldest sibling or the appointed elder leading the family consensus.